Perlindungan Hukum Terhadap Adat Pamali Kekerasan Dalam Rumah Tangga - Wadjo, Hadibah Zachra; Wessy, Yeheskel; Noya, Stelvia Wemly; Ririhena, Michael (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Domestic violence is prohibited because it has an impact from the private sphere to the public domain. It is inevitable, that the problem of domestic violence for some people is still seen as a disgrace in the family, so it is not worthy of being known by society in the social environment.Purposes of Devotion: To increase public awareness about the Importance of Legal Protection Against Customary